THE USE OF PUBLIC RELATIONS IN PROJECTING AN ORGANIZATION'S POSITIVE IMAGE - Ioana Olariu (Studies and Scientific Researches: Economics Edition, 2017)
This article is a theoretical approach on the importance of using public relations in helping an organization to project a positive image. The study of the impact information has on the image of organisations seems to be an interesting research topic. Practice has proved that the image of institutions has a patrimonial value and it is sometimes essential in raising their credibility. It can be said that an image is defined as the representation of certain attitudes, opinions or prejudices concerning a person, a group of persons or the public opinion concerning an institution. In other words, an image is the opinion of a person, of a group of persons or of the public opinion regarding that institution. All specialists agree that a negative image affects, sometimes to an incredible extent, the success of an institution. In the contemporary age, we cannot speak about public opinion without taking into consideration the mass media as a main agent in transmitting the information to the public, with unlimited possibilities of influencing or forming it. The plan for the PR department starts with its own declaration of principles, which describes its roles and contribution to the organisation.